PERMAINAN ENGKLEK TERHADAP KEMAMPUAN MOTORIK ANAK AUTIS DI TAMAN KANAK-KANAK - Kusuma, Adelina (Jurnal Pendidikan Khusus, 2017)
Abstract: Children with autism who experience obstacles in rough motor skills that jump on one foot, leg muscles are less strong and poor body balance, should be given a game that can attract interest, attention as well as able to train the abusive motor skills of children. Hopscotch game is a game requires the player to jump with one leg resting on. Aspects developed in this study are the strength of the foot in a jump on one foot, the accuracy in jumping with one foot on a specified area and maintain balance. The research method in this research is by using quantitative research approach to the type of pre-experimental study, and the study design one-group pretest-posttest design. Subjects in this study, namely 6 autistic children aged 4-5 years in kindergarten Mentari School Sidoarjo, the purpose of this research is to prove the influence of hopscotch game against the gross motor skills of children with autism in kindergarten Mentari School Sidoarjo. Data collection techniques using action tests on gross motor skills and observation. While the data analysis techniques use non parametik statistics with marked rank test.The results showed that the initial test / pre-test average obtained was 50 and was given treatment after the final test / post-test with an average of 80.5 obtained for this case shows that there is a significant increase. Zh value = 2.20 is greater than 5% value crisis Zt = + 1.96, which means that Ho refused and Ha is received so that it can be said of the influence of hopscotch game against the gross motor skills of children with autism in kindergarten Mentari School Sidoarjo.   Keywords: hopscotch game, Motor Rough